Children Growth And Development Of 18 Months-Aged Babies: Nutritional Status Overview For Early Stunting Screening - Retno Apriliyanti; Dwi Kustriyanti (Jurnal Smart Keperawatan, 2023)
Problems in toddlers include nutrition that can cause malnutrition and stunting. The prevalence of stunting in Indonesia based on the results of the Nutrition Status Monitoring reached 27.5%, while undernourished was 16.29% and underweight babies reached 7.44%. The privilege case in Rowosari, there are 28 children with stunting in 2022. The purpose of this study was to figure out the description of children growth and development at the Rowosari Health Center Semarang for early stunting detection. This type of research was descriptive with a cross-sectional approach. 35 infants under 18 months of age were assessed for nutritional status and stunting by calculating the Z-score and the education and occupation factors of the mother were also analyzed using the chi-square test. The results showed that 5.7% of infants were malnourished and 20% over-nourished, and 17.1% were short and 2.9% were very short.   There is a relationship between nutritional status on stunting with p-value <0.05.Keywords: growth; nutritional status; stuntingPertumbuhan Dan Perkembangan Anak Bayi Umur 18 Bulan: Gambaran Status Gizi Untuk Skrining Stunting DiniABSTRAKMasalah pada balita antara lain gizi yang dapat menyebabkan gizi buruk dan stunting. Prevalensi stunting di Indonesia berdasarkan hasil Pemantauan Status Gizi mencapai 27,5%, sedangkan gizi kurang 16,29% dan bayi kurus mencapai 7,44%. Kasus keistimewaan di Rowosari, terdapat 28 anak stunting pada tahun 2022. Tujuan penelitian ini adalah untuk mengetahui gambaran tumbuh kembang anak di Puskesmas Rowosari Semarang untuk deteksi dini stunting. Jenis penelitian ini adalah deskriptif dengan pendekatan cross sectional. 35 bayi berusia di bawah 18 bulan dinilai status gizi dan stuntingnya dengan menghitung Z-score serta faktor pendidikan dan pekerjaan ibu juga dianalisis menggunakan uji chi-square. Hasil penelitian menunjukkan bahwa 5,7% bayi mengalami gizi buruk dan 20% gizi lebih, serta 17,1% bayi pendek dan 2,9% bayi sangat pendek. Ada hubungan antara status gizi dengan stunting dengan p-value < 0,05.Kata kunci: pertumbuhan; status gizi; stunting